2016
DOI: 10.1530/joe-15-0424
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetic transcriptomic profiling of microdissected human trophoblast

Abstract: Gestational diabetes mellitus (GDM), the most common metabolic complication of pregnancy, is influenced by the placenta, and its prevalence directly increases with obesity. Therefore, to define the aetiology of GDM requires that the confounding influence of obesity and the heterogeneous nature of the placenta impairing accurate quantitative studies be accounted for. Using laser capture microdissection (LCM), we optimized RNA extraction from human placental trophoblast, the metabolic cellular interface between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A small study assessing placental gene expression (using a metabolic gene array) in women with type 1 diabetes, obese women with gestational diabetes and women without diabetes, showed differential regulation of lipid-metabolism related genes in the women with gestational diabetes [46]. More recent studies have tried to discriminate the effects on gene expression caused by gestational diabetes itself and those associated with obesity, revealing upregulation in gestational diabetes of genes involved in RNA processing and splicing [47], as well as divergent expression of genes such as mTOR and AMPK [48]. Placental miRNA expression in gestational and pre-gestational diabetes is reviewed in Section 2.3 and Section 2.4.…”
Section: Mirnasmentioning
confidence: 99%
“…A small study assessing placental gene expression (using a metabolic gene array) in women with type 1 diabetes, obese women with gestational diabetes and women without diabetes, showed differential regulation of lipid-metabolism related genes in the women with gestational diabetes [46]. More recent studies have tried to discriminate the effects on gene expression caused by gestational diabetes itself and those associated with obesity, revealing upregulation in gestational diabetes of genes involved in RNA processing and splicing [47], as well as divergent expression of genes such as mTOR and AMPK [48]. Placental miRNA expression in gestational and pre-gestational diabetes is reviewed in Section 2.3 and Section 2.4.…”
Section: Mirnasmentioning
confidence: 99%
“…miR876 has been found to be elevated in type 1 diabetes patient (Satake et al 2018). It has also been showed that miR876-5p is elevated in human trophoblast during gestational diabetes (Bari et al 2016). However, from these studies, it will be premature to conclude the role of miR-876 in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). For instance, studies addressing invasion of the extravillous trophoblast into the maternal decidua sample the basal plate ( Winn et al , 2009 ), while those investigating the maternal–foetal transfer across the syncytiotrophoblast would sample the villous placenta ( Bari et al , 2016 ). Unwanted variation may arise from inappropriate sampling of the placenta, such as non-removal of the decidua for studies of the villous placenta, inclusion of infarcted areas and insufficient cleaning to remove excess blood.…”
Section: Important Considerations For Placental Transcriptome Studiesmentioning
confidence: 99%
“…Studies have also considered other forms of diabetes in pregnancy, such as pre-existing type I and type II diabetes ( Radaelli et al , 2009 ; Alexander et al , 2018 ) or tried to account for differences in maternal obesity, which is more common in diabetic groups compared with controls ( Bari et al , 2016 ). However, as the numbers of each diabetic type or BMI group are small, more studies are needed to confirm if the identified differences are due to diabetes or obesity.…”
Section: Placental Transcriptome Studies Of Pregnancy Complicationsmentioning
confidence: 99%